Liquidambar orientalis Mill. gum extract induces autophagy via PI3K/Akt/mTOR signaling pathway in prostate cancer cells. Issue 5 (4th May 2022) - Atmaca, Harika; Camli Pulat, Cisil; Cittan, Mustafa
ABSTRACT: Liquidambar orientalis Mill (LOM), is an endemic species having a local distribution in the southwestern coastal district of Turkey. Styrax liquidus gum (SLG), is a gum-like resinous which exudates in response to injury of the trunk of LOM. The aim of the study was to investigate the cytotoxic effects and the molecular mechanisms of the ethanolic SLG extract in human prostate cancer cells. GC-MS analysis was performed to identify the volatile compound composition. Cytotoxicity was determined by XTT analysis. Apoptosis and necrosis were evaluated via ELISA assay. Autophagic cell death was detected via monodansylcadaverine (MDC) staining and by measuring the levels of LC3I and LC3II. The protein levels of p-PI3K, p-Akt and p-mTOR were evaluated by western blot analysis. In the present study, it is shown that the SLG extract containing a considerable amount of ravidomycin derivate induced autophagic cell death in prostate cancer cells via inhibiting the PI3K/Akt/mTOR pathway.